Study on the influence mechanism of perceived benefits on unsafe behavioral decision-making based on ERPs and EROs - Zhang, Shu; Yang, Qiyu; Wei, Cong; Shi, Xiuzhi; Zhang, Yan (Frontiers in Neuroscience, 2023)
In order to explore the underlying influence mechanism of perceived benefits in the decisionmaking process of unsafe behaviors, the role of perceived benefits in the decision-making of unsafe behaviors was studied from the perspective of neuroscience. We utilized the "One Stimulus-Two Key Choice (S-K1/K2)" experimental paradigm to design an EEG experiment. In the experiment, participants were asked to make decisions in risky scenarios under high perceived benefits (HPB), low perceived benefits (LPB), and control conditions (CC). The recorded EEG data were applied time domain analysis and time-frequency analysis to extract ERPs (event-related potentials) and EROs (event-related oscillations), which include P3 component, theta oscillations, alpha oscillations, and beta oscillations. The findings suggested that: 1) The theta and alpha oscillations were significantly different under the LPB and HPB conditions compared to the CC. 2) Under the HPB condition, individuals were attracted to perceived benefits, leading to a reduction in internal attention. Additionally, high perceived benefits evoked individuals' positive emotions and motivation, leading individuals to underestimate risk. Consequently, they exhibited a greater inclination towards unsafe behaviors. 3) Under the LPB condition, individuals faced certain losses, leading to a reduction in memory review, resulting in a simple decision-making process, and they were more inclined to make fast decisions to avoid loss. Consequently, they exhibited more safe behaviors. The research results can help to provide targeted intervention measures, which are beneficial to reducing workers' unsafe behaviors.